Presumed Group B Streptococcal Meningitis After Epidural Blood Patch. (15th June 2015) - Beilin, Yaakov; Spitzer, Yelena
Abstract : Bacterial meningitis after epidural catheter placement is rare. We describe a case in which a parturient received labor epidural analgesia for vaginal delivery complicated by dural puncture. The patient developed postdural puncture headache and underwent 2 separate epidural blood patch procedures. She subsequently developed a headache with fever and focal neurologic deficits. She was treated with broad spectrum antibiotics for presumed meningitis, and she made a full recovery. Blood cultures subsequently grew group B streptococcus.